PENERAPAN METODE AGILE PADA AUGMENTED REALITY (AR) BERBASIS CERITA BUDAYA KARANGKAMULYAN DI KABUPATEN CIAMIS - Fathiyia Rahma, Wafa; Mulyana , Dadan; Sidiq, Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
Cultural tourism plays an important role in preserving local historical and cultural tourism. However, young people's interest in cultural tourism is declining due to a lack of interesting information media. This study aims to design Augmented Reality (AR)-based information media at the Karangkamulyan Site, Ciamis Regency, to make cultural presentations more interesting and useful. The method used in this design is the Agile method. This study focuses on three main stages, namely planning, design, and development. Planning is carried out through interviews and literature studies, design includes product backlog and sprint planning, while the development stage produces wireframes and UML diagrams.  The research results are the wireframe design of an AR application that has features such as AR Virtual Tour, About the Site, Site Map, Events, Facilities, and Feedback. This design is expected to increase the interest of the younger generation in cultural tourism.